2020
DOI: 10.18295/squmj.2020.20.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Musculoskeletal Symptoms in Otorhinolaryngology-Head and Neck Surgery Residents

Abstract: Objectives: Work-related musculoskeletal disorders in Saudi Arabia are not often reported in the literature. This study aimed to identify musculoskeletal symptoms among otorhinolaryngology residents in Saudi Arabia. Methods: This cross-sectional survey-based study was conducted in May 2018 and included residents registered in the Saudi Otorhinolaryngology-Head and Neck Surgery Board Training programme, Riyadh, Saudi Arabia. The Nordic Musculoskeletal Questionnaire was used to assess musculoskeletal symptoms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Of the 1121 articles initially reviewed by title and/or abstract, 20 were selected for full-text screening. Fifteen studies were cross-sectional surveys 6,8,[11][12][13][14][15][16][17][18][19][20][21][22][23] six were observational or had an observational arm, 17,18,[24][25][26][27] and one was a randomized controlled trial 28 (Table II). Twenty studies (involving 2881 participants) met criteria for qualitative discussion and 10 studies (involving 1846 participants) met criteria for meta-analysis (Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 1121 articles initially reviewed by title and/or abstract, 20 were selected for full-text screening. Fifteen studies were cross-sectional surveys 6,8,[11][12][13][14][15][16][17][18][19][20][21][22][23] six were observational or had an observational arm, 17,18,[24][25][26][27] and one was a randomized controlled trial 28 (Table II). Twenty studies (involving 2881 participants) met criteria for qualitative discussion and 10 studies (involving 1846 participants) met criteria for meta-analysis (Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…1). Fifteen studies reported rates and subsites of WRMD 6,8,[11][12][13][14][15][16][17][18][19][20][21][22][23] and six studies included ergonomic assessment in the form of the Rapid Upper Limb Assessment tool (RULA). 17,18,[24][25][26][27] Included studies were published between 2003 and 2020.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…3,44,45 Rates of pain among trainees are .90% in some studies. 2,45,46 Residents typically work longer hours than attending physicians and have less time for recovery. Additionally, residents tend to adopt surgical positions based on observation of their mentors and personal preference rather than ergonomic principles.…”
Section: Discussionmentioning
confidence: 99%
“…Trainees in otolaryngology are not immune from this issue, as it has been well established that symptoms of WRMD begin early in residency 3,44,45 . Rates of pain among trainees are >90% in some studies 2,45,46 . Residents typically work longer hours than attending physicians and have less time for recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation